Medication safety officer preparatory course: Outcomes and experiences - Hisham Aljadhey; Salma Alkhani; Tahir Mehmood Khan (Elsevier, 2017)
Purpose: Few hospitals employ a medication safety officer. A medication safety officer preparatory course was planned using a structured curriculum to prepare pharmacists with the knowledge and skills to start medication safety officer activities. The current study aims to assess the outcome, as change in knowledge, of a hospital medication safety officer preparatory course. Methods: We conducted a three-day course in February 2011 in Riyadh, Saudi Arabia. It was developed to provide attendees with the essential knowledge and skills to become a medication safety officer. Teaching methodologies included didactic teaching, group discussions, case presentations, and an independent study of medication safety materials. The content of the course focused on the various roles of a medication safety officer, the importance of medication safety in a health care setting, the incidence of adverse drug events in a hospital setting, strategies to identify and prevent adverse events, the use of root cause analysis and failure mode and effect analysis, the role of an officer in hospital accreditation, and ways for promoting safety culture. Assessment of the course outcome was accomplished by comparing scores of knowledge level before and after the course. The knowledge level was assessed by a 20-item exam which was developed and validated by course instructors. Results: Twenty-one participants attended the course and completed both the baseline and after-course assessment questionnaires. The majority was male (N = 14, % = 66.7) with a job experience of 1-5 five years (N = 10, % = 47.6). The knowledge score increased from 14.3 ± 1.90 (mean ± standard deviation) at baseline to 18.5 ± 1.43 after successfully completing the course (P < 0.001). Conclusion: A three-day medication safety officer preparatory course has been shown to significantly improve attendee knowledge about medication safety. Educating health care professionals is an important tool to help ensure the safety of patients.